Surgical therapy in duodenal-jejunal hemorrhagic diverticula, case report and bibliographic review.: Terapéutica quirúrgica en divertículos duodeno-yeyunales hemorrágicos, reporte de caso y revisión bibliográfica. | 十二指肠-空肠出血性憩室的外科治疗：病例报告和文献综述 - Trinidad Rodríguez, Williams (2024)
Summary: Introduction: Diverticula are intestinal saccular dilations; They can be classified as false or true, congenital or acquired. Complications can be serious, bleeding is the most characteristic sign. Case report: Female, 68 years old, the condition began with upper digestive bleeding, endoscopic studies did not show any bleeding site; intestinal transit reported 2 duodenal diverticula. Due to multiple transfusions and hospitalizations, surgery was scheduled. Two duodenal diverticula and multiple diverticula were found in the jejunum. Duodenal diverticulectomies and segmental resection of the jejunum with entero-entero anastomosis were performed. During the post-surgery period she presented intestinal fistula, which was resolved with mixed nutrition. Discussion: Intestinal transit revealed diverticula as a probable cause of bleeding. Since there were no minimally invasive options as determined by the guidelines, less morbid surgical treatment was provided. Conclusions: In the absence of endoscopic or endovascular options, surgical intervention is a viable option; however, each case must be individualized to offer the lowest morbidity and mortality rate.